An all-in-one adjuvanted therapeutic cancer vaccine targeting dendritic cell cytosol induces long-lived tumor suppression through NLRC4 inflammasome activation. (July 2022) - Puth, Sao; Verma, Vivek; Hong, Seol Hee; Tan, Wenzhi; Lee, Shee Eun; Rhee, Joon Haeng
Abstract: Therapeutic cancer vaccines (TCVs) should induce robust tumor-specific T cell responses. To achieve this, TCVs incorporate T cell epitopes and strong adjuvants. Here, we report an all-in-one adjuvanted cancer vaccine platform that targets the intracellular compartment of dentritic cells and subsequently induces effective cytotoxic T cell responses. We screened a novel peptide (DCpep6) that specifically binds and transmits into CD11c + cells through a novel in vivo phage biopanning. We then engineered a protein-based TCV (DEF) consisting of DCpep6 (D), an optimized HPV E7 tumor antigen (E), and a built-in flagellin adjuvant (F) as a single molecule. DEF was stably expressed, and each component was functional. In vivo -administered DEF rapidly biodistributed in draining LNs and internalized into CD11c + cells. DEF immunization elicited strong antitumor T cell responses and provided long-term survival of TC-1 tumor-implanted mice. The DEF-mediated antitumor effect was abolished in NLRC4 −/− mice. Taken together, we propose a protein-based all-in-one TCV platform that intracellularly codelivers tumor antigen and inflammasome activator to DCs to induce long-lasting antitumor T cell responses.